Men Passionately Pursuing Purpose (MP3): A Group Counseling Intervention for Black Male Student Athletes. Issue 2 (2nd April 2020) - Harris, Paul C.; Mayes, Renae D.; Freeman, Carol; Eberly, Brian; Tatby, Najwa; Wiener, Sarah
ABSTRACT: Black male student athletes are at risk for over-identification with their athletic role to the detriment of their other identities. This paper describes a study that explored the meaning ascribed by high school Black male student athletes to an 8-week group counseling experience. Semi-structured interviews were conducted with participants after the group experience and two major themes emerged: sense of self and connection with others/brotherhood. Implications for school counselors are discussed.